El reflejo del Sínodo en las portadas de la iglesia de Santa María de Aguilafuente (Segovia) - Moreno Alcalde, María (Anales de Historia del Arte, 2007)
Two gothic façades were added in the fifteenth century to the primitive Romanesque building of the parish church of Aguilafuente in Segovia. A diocesan synod took place in this church in 1472, and its minutes where printed. They are the first incunabula written in Spanish. This paper establishes a relationship between these two events, and presents the building of these façades as a consequence of that synodal meeting.